2016
DOI: 10.1073/pnas.1616264113
|View full text |Cite
|
Sign up to set email alerts
|

Interface-induced superconductivity at ∼25 K at ambient pressure in undoped CaFe 2 As 2 single crystals

Abstract: Superconductivity has been reversibly induced/suppressed in undoped CaFe 2 As 2 (Ca122) single crystals through proper thermal treatments, with T c at ∼25 K at ambient pressure and up to 30 K at 1.7 GPa. We found that Ca122 can be stabilized in two distinct tetragonal (T) phases at room temperature and ambient pressure: PI with a nonmagnetic collapsed tetragonal (cT) phase at low temperature and PII with an antiferromagnetic orthorhombic (O) phase at low temperature, depending on the low-temperature annealing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…It was later found 2328 that the undoped single-crystalline Ca122 can stabilize in two slightly different non-superconducting tetragonal phases (PI and PII) after rapid quenching from 850 °C and prolonged annealing at 350 °C, respectively. The PI phase corresponds to a tetragonal (T) structure at room temperature [lattice parameter c = 11.547(1) Å], and transforms to a collapsed-tetragonal (cT) phase with a 10% shorter c -lattice [ c = 10.720(1) Å] below the T-cT structural transition temperature (T cT ) around 100 K. On the other hand, the PII phase also exhibits a tetragonal structure at room temperature but with a slightly longer c [ c = 11.763(1) Å].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was later found 2328 that the undoped single-crystalline Ca122 can stabilize in two slightly different non-superconducting tetragonal phases (PI and PII) after rapid quenching from 850 °C and prolonged annealing at 350 °C, respectively. The PI phase corresponds to a tetragonal (T) structure at room temperature [lattice parameter c = 11.547(1) Å], and transforms to a collapsed-tetragonal (cT) phase with a 10% shorter c -lattice [ c = 10.720(1) Å] below the T-cT structural transition temperature (T cT ) around 100 K. On the other hand, the PII phase also exhibits a tetragonal structure at room temperature but with a slightly longer c [ c = 11.763(1) Å].…”
Section: Introductionmentioning
confidence: 99%
“…It undergoes a tetragonal-to-orthorhombic (T-O) transition [ c = 11.653(1) Å] at the T-O structural transition temperature (T O ) around 170 K. The orthorhombic phase is ordered antiferromagnetically, and the T-O transition is closely related to the spin-density-wave transition. It was found that the PI and PII phases could be reversibly transformed by heat treatment 28 . Microscopic techniques were also utilized to reveal the homogeneity and strain effect in the Ca122 annealed at different temperatures 23,24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of the superconductivity in the Ca122 compounds is still unclear, but numerous results have suggested that an adequate Fe magnetic moment is crucial to mediating Cooper pairs in the compounds 1,2,4 . The interface superconductivity that emerges in undoped Ca122 has been reported to originate from the interface between the collapsed tetragonal (cT) and orthorhombic (O) phases or between the AFM antiphase domain boundaries 32,33 . For undoped and Co-doped Ca122, nuclear magnetic resonance (NMR) results suggest that FM fluctuations compete with superconductivity but can coexist with a stripe-type AFM phase 34 .…”
Section: Discussionmentioning
confidence: 99%
“…This motivates our studies. We found [10] that Ca122 quenched from 850 °C or above has a tetragonal structure at room temperature (P 1 phase), but transforms to a collapsed-tetragonal phase with a 10% shorter c lattice parameter below T cT , the T-cT transition temperature [11]. No magnetic ordering is detected over the whole temperature range.…”
Section: Interface-induced Superconductivitymentioning
confidence: 99%